The comparison of the effectiveness of the lowest supply lowest cost (LSLC) algorithm and the exponential approach algorithm in transportation problems - Purba, Tresya Carmela; Notiragayu, Notiragayu; Fitriani, Fitriani; Azis, Dorrah (Universitas Islam Negeri Raden Intan Lampung, 2021)
Transportation problems are one of the particular forms that often appear in linear programs, one of which is the distribution of goods. A transportation method is needed to determine the optimal result, namely, the minimum cost from source to destination with all demand and supply fulfilled. There are several methods, one of which is the Lowest Supply Lowest Cost Method (LSLC) and the Exponential Approach Method (PE). Both methods are made in a MATLAB program, generating a script that calculates the algorithm's time complexity. Using the function notation, the Big-O Algorithm complexity of the Lowest Supply Lowest Cost method is more efficient than the Exponential Approach Method algorithm. At the same time, the optimal result for the minimum cost between the two methods is obtained by using the Exponential Approach Method.